Influence of Activin A Supplementation During Human Embryonic Stem Cell Derivation on Germ Cell Differentiation Potential - Duggal, Galbha (Mary Ann Liebert, Inc., 2013)
Human embryonic stem cells (hESCs) are more similar to “primed” mouse epiblast stem cells (mEpiSCs). mEpiSCs, which are derived in Activin A, show an increased propensity to form primordial germ cell (PGC)-like cells in response to bone morphogenic protein 4 (BMP4). Hence, we hypothesized that hESCs derived in the presence of Activin A may be more competent in differentiating towards PGC-like cells after supplementation with BMP4 compared to standard hESC lines. We were able to successfully derive two hESC lines in the presence of Activin A, which were pluripotent and showed higher base levels of STELLA and cKIT compared to standard hESC lines derived without Activin A addition. Furthermore, upon differentiation as embryoid bodies in the presence of BMP4, we observed upregulation of VASA at day 7, both at the transcript and protein level compared to standard hESC lines, which appeared to take longer time for PGC specification. Unlike other hESC lines, nuclear pSMAD2/3 presence confirmed that Activin signalling was switched on in Activin A-derived hESC lines. They were also responsive to BMP4 based on nuclear detection of pSMAD1/5/8 and showed endodermal differentiation as a result of GATA-6 expression. Hence, our results provide novel insights into the impact of hESC derivation in the presence of Activin A and its subsequent influence on germ cell differentiation potential in vitro.